Cultivation-Independent Characterization of Methylobacterium Populations in the Plant Phyllosphere by Automated Ribosomal Intergenic Spacer Analysis - Knief, Claudia (American Society for Microbiology (ASM), 2008)
Bacteria of the genus Methylobacterium are widespread in the environment, but their ecological role in ecosystems, such as the plant phyllosphere, is not very well understood. To gain better insight into the distribution of different Methylobacterium species in diverse ecosystems, a rapid and specific cultivation-independent method for detection of these organisms and analysis of their community structure is needed. Therefore, 16S rRNA gene-targeted primers specific for this genus were designed and evaluated. These primers were used in PCR in combination with a reverse primer that binds to the tRNA(Ala) gene, which is located upstream of the 23S rRNA gene in the 16S-23S intergenic spacer (IGS). PCR products that were of different lengths were obtained due to the length heterogeneity of the IGS of different Methylobacterium species. This length variation allowed generation of fingerprints of Methylobacterium communities in environmental samples by automated ribosomal intergenic spacer analysis. The Methylobacterium communities on leaves of different plant species in a natural field were compared using this method. The new method allows rapid comparisons of Methylobacterium communities and is thus a useful tool to study Methylobacterium communities in different ecosystems.